Stellate Genes and the piRNA Pathway in Speciation and Reproductive Isolation of Drosophila melanogaster - Adashev, Vladimir E.; Kotov, Alexei A.; Bazylev, Sergei S.; Shatskikh, Aleksei S.; Aravin, Alexei A.; Olenina, Ludmila V. (Frontiers in Genetics, 2021)
One of the main conditions of the species splitting from a common precursor lineage is the prevention of a gene flow between diverging populations. The study of Drosophila interspecific hybrids allows to reconstruct the speciation mechanisms and to identify hybrid incompatibility factors that maintain postzygotic reproductive isolation between closely related species. The regulation, evolution, and maintenance of the testis-specific Ste-Su(Ste) genetic system in Drosophila melanogaster is the subject of investigation worldwide. X-linked tandem testis-specific Stellate genes encode proteins homologous to the regulatory β-subunit of protein kinase CK2, but they are permanently repressed in wild-type flies by the piRNA pathway via piRNAs originating from the homologous Y-linked Su(Ste) locus. Derepression of Stellate genes caused by Su(Ste) piRNA biogenesis disruption leads to the accumulation of crystalline aggregates in spermatocytes, meiotic defects and male sterility. In this review we summarize current data about the origin, organization, evolution of the Ste-Su(Ste) system, and piRNA-dependent regulation of Stellate expression. The Ste-Su(Ste) system is fixed only in the D. melanogaster genome. According to our hypothesis, the acquisition of the Ste-Su(Ste) system by a part of the ancient fly population appears to be the causative factor of hybrid sterility in crosses of female flies with males that do not carry Y-linked Su(Ste) repeats. To support this scenario, we have directly demonstrated Stellate derepression and the corresponding meiotic disorders in the testes of interspecies hybrids between D. melanogaster and D. mauritiana. This finding embraces our hypothesis about the contribution of the Ste-Su(Ste) system and the piRNA pathway to the emergence of reproductive isolation of D. melanogaster lineage from initial species.